The development of a competency-based programme for management of disease outbreaks - Engelbrecht, Linette (University of the Witwatersrand, Johannesburg, 2024)
Purpose: The purpose of this study was to develop, a competency-based programme for the management of disease outbreaks. Method: The study utilized an exploratory sequential mixed method approach, using both qualitative and quantitative methods to develop a competency-based program. This study was conducted in South Africa, Gauteng, whilst the country was experiencing the third COVID-19 wave (May 2021 – October 2021), the fourth COVID-19 wave (December 2021– April 2022), and the fifth (May 2022 – July 2022), as well as the post-pandemic phase. The study was conducted in three phases namely: Phase One: Exploratory phase, Phase Two- Development of the programme Phase Three- Validation of the programme. In phase one, a scoping review on the existing literature was conducted using the Joanna Briggs Institute methodological approach. Following this were individual in-depth interviews with purposively sampled healthcare professionals as well as professional nurses. Through reflexive thematic analysis themes were identified for inclusion in the Delphi-survey in the next phase. For the second phase, a Delphi-survey was developed based on the data from phase one. The Delphi-survey consisted of two rounds whereby categories were identified to be included in the competency-based curriculum. A curriculum, consisting of ten modules was developed using the Backward design. In phase three the curriculum matrix was validated by experts. Results: A total of 62 publications were included in this study. Three categories and eight sub-categories were identified as needs of nurses during disease outbreaks. In-depth interviews with healthcare professionals resulted in the development of eight themes and 21 sub themes (challenges) of nurses. The in-depth interviews with nurses resulted in the development of 11 themes (challenges) of nurses. The results of the scoping review and in- depth interviews were used to develop a Delphi-survey. Experts in this two-round Delphi survey validated the domains and statements. The results of the Delphi-survey was used to develop a curriculum matrix consisting of ten modules, which was validated by three experts. Conclusion: A competency- based curriculum was developed based on the challenges nurses experienced working through the COVID-19 pandemic. This program could contribute to the development of disease outbreak competent nurses
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements of the degree of Doctor of Philosophy Johannesburg, 2024
Keywords: Competency-based programme; Disease outbreak; COVID-19; Challenges; Nurses; UCTD; SDG-3: Good health and well-being